Good or Bad Financial Reporting Can Cause Changes in Company Management - Safkaur, Otniel; Nurafiah, Nunuy; Paulus, Sugiono; Dahlan, Muhammad (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to determine the effect of earnings management on financial performance. The company's reported profit is not clear because complex interactions include three factors, namely managerial motivation, accounting standards, and the application of accounting standards. Managers have the desire to manage company earnings reports using accrual policies that are permitted by accounting standards with the aim of covering company performance. Accrual accounting aims to help users of corporate financial statements in assessing economic performance during a period through the use of accounting principles, such as the use of accounting for recognition of income and expenses. The unit of analysis in this study is industrial companies in Papua-Indonesia. The results of the study indicate that earnings management has a significant effect on financial performance. Furthermore, it was found that earnings management can change because it affects the financial performance survey of companies of state-owned enterprises in Papua in Indonesian. Keywords: Profit Management, Financial Performance, earnings management JEL Classification: G2 DOI: https://doi.org/10.32479/ijefi.8467